2014
DOI: 10.1155/2014/945645
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition of Carbon Steel in 0.5 M H2SO4by Phtalocyanine Blue

Abstract: Phthalocyanine blue dye has been investigated as a carbon steel corrosion inhibitor in 0.5 M sulfuric acid by using polarization curves, electrochemical impedance spectroscopy, and gravimetric tests. Dye concentrations included 0, 100, 200, 400, 600, 800, and 1000 ppm, whereas testing temperatures were 25, 40, and 60 ∘ C. Results indicated that phtalocyanine blue is a good corrosion inhibitor with its efficiency increasing with the concentration up to 40 ∘ C, but it increases at 60 ∘ C. Inhibitor improves the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The addition of 10 and 100 ppm presented the formation of passive zones at the potentials of −79 mV and −185 mV, respectively. The improvement in the corrosion behavior of the steel in the present study can be associated with the enhanced properties of the passive film due to the interaction between the molecules of inhibitor and corrosion products, decreasing the anodic dissolution rate of the steel surface (9,24).…”
Section: Polarization Curvesmentioning
confidence: 63%
See 1 more Smart Citation
“…The addition of 10 and 100 ppm presented the formation of passive zones at the potentials of −79 mV and −185 mV, respectively. The improvement in the corrosion behavior of the steel in the present study can be associated with the enhanced properties of the passive film due to the interaction between the molecules of inhibitor and corrosion products, decreasing the anodic dissolution rate of the steel surface (9,24).…”
Section: Polarization Curvesmentioning
confidence: 63%
“…After 3 h of tests, it was observed a quasistable behavoir of the LPR curves of the 1018 steel electrode using different concentrations of inhibitor, exepecting for 10 ppm, which reached its stability after 16 h. The steady state of the corrosion process revealed the protective nature of the inhibitor, forming a film that can modify the properties of the metallic surface. Firstly, the inhibitor can block active sites in short periods of time, and subsequently, at longer periods of time, this can produce a geometric obstruction, that is, the effect of inhibition is originated from the reduction of the reaction area of the metallic surface (20,24). On the other hand, the test performed without inhibitor presented an unstable behavoir.…”
Section: Linear Polarization Resistance (Lpr)mentioning
confidence: 99%
“…The single semicircle indicates that the corrosion process is charge transfer control from the mild steel to the corrosive medium through the electrochemical double layer. The real axis intercepts at high and low frequencies are bigger in the presence of mixture A and B, which means that the impedance of the mild steel in the inhibited solutions is greater than the uninhibited solution 30 .…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Earlier studies by several researchers reported that some organic dyes are quite effective in retarding the corrosion of iron and steel in aggressive acid environments [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Thus, some work were evaluated the use of Azorubine, Sunset Yellow, Amaranth, Allura Red, Tartrazine, Fast Green, Nile Blue, Indigo Carmine, Red cabbage, Natural Kermes, Safranin, as corrosion inhibitors for mild steel in hydrochloric acid solutions [12][13][14][15][16][17], although, some dyes, as Congo red, Bismark brown, Malachite green and Naphthol, were also investigated for aluminum surface in hydrochloric acid [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Cresol red, Methyl violet, and Alizarin violet have been used as well for the corrosion inhibition of cold rolled steel in acidic solution [22][23][24]. Additionally, Alizarin yellow, Bromophenol blue, Thiophene azo, Phtalocyanine Blue and Acid red GRE, have also been studied as corrosion inhibitors for carbon steel in acidic environments [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%